Evaluation of Kidney Dose in Neuroendocrine Tumors Patients after Peptide Receptor Radionuclide Therapy using 177Lu-DOTATATE - N.R. Hidayati; A. Poon; K. Willowson; E. Eslick; H. Ryu; D.L. Bailey (Atom Indonesia, 2019)
Radiation dose to the kidneys (kidney dose) in 177Lu-DOTATATE - Peptide Receptor Radionuclide Therapy(PRRT) is considered to be the main potential side-effect from the treatment. Prospective assessment of kidney radiation dose can be made with SPECT, however, this requires an intensive imaging regime over a number of days. For this reason, a retrospective investigation of kidney uptake using quantitative SPECT was performed. The aim of the study was to compare the estimated radiation dose to kidneys for each cycle. Seventeen patients treated with 177Lu-DOTATATE for metastatic neuro-endocrine tumors had full imaging for each of their treatment cycles on a Siemens Intevo SPECT/CT gamma camera. One course of treatment consisted of 3 or 4 cycles approximately 8 weeks apart spanning 6 months. SPECT/CT scans of the abdomen were acquired at 3 time points (4, 24 and 96-120 hours) after administration of ~7.8 GBq of 177Lu-DOTATATE. Nine patients received three cycles in total and eight patients had four cycles. Volumes of interest (VOIs) were defined on a CT scan co-registered with the SPECT images and repeated over all time points, to give the radioactivity in the kidneys. Whole organ dosimetry was estimated using OLINDA/EXM using an exponential clearance model. This gives an estimate of radiation absorbed dose to kidneys, in the unit of absorbed dose of organ per administered activity(Gy/GBq) for each treatment cycle. The mean of the 3 or 4 cycles and variation can then be determined. The result shows that the average kidney radiation dose was 0.23 Gy/GBq (range: 0.06 – 0.42) and the average variation between cycles  for all subjects expressed as a percentage was (12.5±7.8) % (median: 11.4 %, range: 1.8 % - 29.4 %). From this study, it can be concluded that the estimated radiation dose to the kidneys for PRRT shows good reproducibility (typically <20 % variation) within an individual across all cycles within one course of treatment  (up to 4 cycles). The errors introduced by assuming that the dosimetry estimate per unit GBq administered from the initial cycle could be used for subsequent cycles within a course are unlikely to contribute significantly to the overall estimate of radiation burden and are considered to be safe.